A new species of Psydrax (Vanguerieae, Rubiaceae) from Luzon, Philippines including its conservation status - Arriola, Axel Havana; Alejandro, Grecebio Jonathan (Phytotaxa, 2013)
Psydrax puberula, a new species from the Philippines is here described and illustrated. It can easily be distinguished from the currently recognized Malesian Psydrax with its puberulent compound umbellate inflorescences with 14–25 flowers as well as a puberulent fruit stalk and fruit. P. puberula is the second species of Psydrax in the Philippines.